Astragaloside IV Reduces Cerebral Ischemia/Reperfusion-Induced Blood-Brain Barrier Permeability in Rats by Inhibiting ER Stress-Mediated Apoptosis. (26th October 2020) - Hou, Bonan; Liu, Rui; Wu, You; Huang, Shuiqing
Abstract : Background . Previous studies proved that AS-IV could prevent blood-brain barrier (BBB) against an increase in permeability. However, its underlying molecular mechanism has not been enlightened yet. The aim of the study is to reveal the potential protective mechanism of astragaloside IV (AS-IV) on the blood-brain barrier after ischemia-reperfusion. Methods . In vivo, AS-IV neurological protection was measured by Long's five-point scale and 2, 3, 5-triphenyltetrazolium chloride staining. AS-IV protection for BBB was observed by Evans blue extravasation technique. Endoplasmic reticulum stress and apoptosis-related protein levels were measured by western blot with AS-IV intervention. In vitro, cell apoptosis was analyzed by western blot and flow cytometry.Endoplasmic reticulum stress-related protein levels were quantified through western blot. Results . AS-IV treatment could decrease the infarct size in rats' brain and protect the BBB against Evans blue permeating through brain, after ischemia/reperfusion, significantly. Further, ischemia/reperfusion or oxygen‐glucose deprivation/reperfusion was found to have an increase in endothelial cell apoptosis proteins, such as Bax, Bcl-2, and caspase-3, and endoplasmic reticulum stress-associated proteins, such as phosphorylated PERK and eIF2 α, Bip, and CHOP, which were attenuated by AS-IV treatment. Conclusions . AS-IV can effectively protect the blood-brain barrier and reduce the area of cerebral infarction via inhibiting endoplasmic reticulum stress-mediated apoptosis in endothelial cells.